PENGARUH UTANG LUAR NEGERI PADA PEMERINTAHAN MEGAWATI SOEKARNOPUTRI, SUSILO BAMBANG YUDHOYONO DAN JOKO WIDODO TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Zikri, Ilman (An Nuqud Journal of Islamic Economics, 2022)
As a developing country, the Indonesian government certainly wants to achieve equitable welfare for its people. However, due to the domestic stock of capital, which of course causes the national economic development process to be hampered, Indonesia is looking for ways to accelerate the national economic development process. One way to do this is that the Indonesian government still relies on foreign debt to finance the national development process. Again, the role of foreign debt on the government of Megawati Soekarnoputri, Susilo Bambang Yudhoyono, and Joko Widodo on economic growth in Indonesia. The nature of this research is quantitative, and the type of data source used is secondary data. The data used include data on economic growth and foreign debt obtained through the official websites of the central statistics agency and bank Indonesia in the 2001-2021 research period. The analytical method used is simple linear regression and uses samples using one of the non-probability sampling techniques, namely purposive sampling. The results of this study explain that the foreign debt of the government of Megawati Soekarnoputri, Susilo Bambang Yudhoyono, and Joko Widodo has a positive and significant effect on economic growth